Trinidad and Tobago. Significant achievements 2016 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2017)
The main activities carried out by the Institute in Trinidad and Tobago during 2016 are identified, with respect to the needs and interests of the country, strengthening issues such as nutrition, marketing, packaging, labeling, family farming, public policies, beekeeping, animal health, microbiology, forage production, technology, governance and food security. Likewise, support was provided in risk mapping, planning, post-harvest management, quality control, analysis of critical control points, and pest and disease control. Finally, work was done on animal husbandry, on the improvement of value chains for goat milk, honey and tubers.